Vocational education and training (VET) practices: issues and challenges in vocational secondary school - Ahmad, Adnan (2008)
Innovation is an important element for teaching and learning in ensuring that the product is always relevant to current requirement. In vocational education, there are a lot of innovations should be carried out such as management, administration and facilities. In terms of the national corporation to become an industrialized nation the need for vocational education becomes fundamental. The relationship between teacher’s pedagogy beliefs and students learning style can be seen as one mediated through process whereby teacher’s beliefs influence their teaching strategies which will turn influence student’s learning style. It is therefore important in VET to address teacher’s new teaching methods, vocational skills, knowledge and student’s learning style to make the practices in SVS can fulfill the goal of VET in globalization. This paper is to describe the role of Vocational Education Training (VET) for preparation to produce human capital start from the basis level. VET in Malaysia started in secondary school and for specific purposes Vocational Secondary School (VSS) has been designed to fulfill the needs of future workforce. Teachers are the main factors to have systematic and interesting approach for students and stakeholders to make VET in VSS is the main choice of education to developed student carrier pathways. The focused in this paper is what is the practices in VSS can achieved the current and future workforce in flexible manner and at a consistent level of quality. It also to review what does it mean to teach in VET and what makes an effective VET teacher. The factors consists the approach to teach in VET, role of teachers and VET students preferences. In summary, the investigation of VET practices will improve the skills of VET teachers including pedagogy and vocational skills it will provide the effectiveness of teaching.